Minielectrode catheter technology for near zero-fluoroscopy substrate-guided ablation of typical atrial flutter - Betz, Johanna; Vitali-Serdoz, Laura; Buia, Veronica; Walaschek, Janusch; Rittger, Harald; Bastian, Dirk (Heart Rhythm O2, 2021)
Background: MicroFidelity catheter technology may facilitate voltage-guided ablation by high-resolution electroanatomic mapping (HR-EAM) and precisely targeted energy application. Objective: To evaluate the performance of minielectrode (ME) technology for zero-fluoroscopy substrate-guided cavotricuspid isthmus (CTI) ablation. Methods: Eighty-two patients underwent near zero-fluoroscopy substrate-guided CTI ablation using a nonirrigated large-tip catheter with 3 MEs. The CTI was subdivided into 15 electroanatomic segments. Bipolar voltage maps were compared with ME signals. The outcome was compared with a historic cohort of 92 patients who underwent linear ablation. Results: Compared with linear ablation, the substrate-guided approach was associated with an almost halved ablation duration (336 ± 228 vs 649 ± 409 seconds, P < .001), halved radiofrequency energy applied (14.2 ± 10.6 vs 28.6 ± 19.6 kJ, P < .001), and shorter procedure duration (60.8 ± 33.8 vs 76.3 ± 40.9 minutes, P = .008) limiting the extent of energy delivery to 22.7% of the CTI area. HR-EAM visualized 2.03 ± 0.88 conductive pathways with a diameter of 5.35 ± 1.98 mm. A higher number of ME-detected bundles and a larger channel diameter correlated with increased ablation requirements. In 97.6% of the voltage-guided and 88.0% of the linear procedures, fluoroscopy was not used. Conclusion: HR-EAM-based substrate-guided CTI ablation may improve procedural outcome compared with the linear approach. Enhanced identification of discrete conductive pathways correlates with ablation efficacy. The electroanatomic subdivision of the CTI into 15 segments was feasible and may improve the understanding and comparability of anatomic variants and ablation results. Independent of the ablation strategy, modern EAM technology enables safe zero-fluoroscopy procedures in the majority of cases.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Atrial flutter; Catheter ablation; Electroanatomic mapping; Maximum voltage-guided; Zero fluoroscopy